Protected P-element termini suggest a role for inverted-repeat-binding protein in transposase-induced gap repair in Drosophila melanogaster. - Staveley, B.E.; Heslip, T.R.; Hodgetts, R.B.; Bell, J.B. (Genetics, 1995)
P-element transposition is thought to occur by a cut-and paste mechanism that generates a double-strand break at the donor site, the repair of which can lead to internally deleted elements. We have generated a series of both phenotypically stronger and weaker allelic derivatives of vg21, a vestigial mutant caused by a P-element insertion in the 5' region of the gene. Virtually all of the new alleles arose by internal deletion of the parental element in vg21, and we have characterized a number of these internally deleted P elements. Depending upon the selection scheme used, we see a very different spectrum of amount and source of P-element sequences in the resultant derivatives. Strikingly, most of the breakpoints occur within the inverted-repeats such that the last 15-17 bp of the termini are retained. This sequence is known to bind the inverted-repeat-binding protein (IRBP). We propose that the IRBP may act to preserve the P-element ends when transposition produces a double-strand gap. This allows the terminus to serve as a template upon which DNA synthesis can act to repair the gap. Filler sequences found at the breakpoints of the internally deleted P elements resemble short stretches, often in tandem arrays, of these terminal sequences. The structure of the filler sequences suggests replication slippage may occur during the process of gap repair.